Impact of Training on Academic Staff of Tertiary Institutions in Nigeria - Sani Kasimu; Ahmed Nuhu Ahmed (Researchparks Publishing, 2023)
The paper investigated the impact of training on academic staff of federal universities in North-Central Nigeria. This study made use of the descriptive survey research design. Three research questions were raised, and three hypotheses were generated for testing. The target population of the study comprised of all academic staff of four public federal universities in North East Nigeria. The sample size is 200. For the purpose of sampling, the multistage and stratified sampling techniques were used. Out of the population of 2,300 staff, a sample of 200 academic staff was drawn using research advisor. The instrument was structured with 15 items using the 4 point likert type scale of measurement ranging from Strongly Agree (4) to Strongly Disagree (1). Training and Academic staff Questionnaire (TASQ) was used for collecting data for the study. The face and content validity was established after subjecting the instrument to vetting by three experts in the field of education. The reliability of the instrument was ascertained using 30 academic staff who were not part of the study sample used. The reliability coefficient of the instrument of 0.82 was computed using Cronbach Alpha formula to measure the internal consistency of the questionnaire items. The responses of the respondents were presented in simple statistical table and analyzed using frequency counts, percentages, mean (x̅), and grand mean (gx̅). The paper discovered that training has impact on pedagogical skills, research skills and provision of community service skills of academic staff of federal universities in North-East Nigeria. Based on this findings, the paper hereby recommended tertiary institutions manager should create environment whereby academic staff are encouraged to participate massively in workshops, seminars and conferences organised internally and externally. This will not only equip them with new skills, techniques, knowledge and experiences necessary to enhance or build their job performance capacity for teaching, research and provision of community service.